2007
DOI: 10.29309/tpmj/2007.14.04.4805
|View full text |Cite
|
Sign up to set email alerts
|

Infertile Female

Abstract: Objective: To highlight the role of laparoscopy in the diagnosis andmanagement of problems related to infertility. Design: Retrospective, descriptive study. Place & Duration: Departmentof Obstetrics & Gynaecology, Shaikh Zayed Hospital, Federal Postgraduate Medical Institute, Lahore between 1stJanuary 2003 to December 2003. Patients & Methods: Forty three women were selected for laparoscopy, 25 havingprimary infertility and 18 having secondary infertility. Results: Laparoscopy diagnosed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The numerous reproductive issues seen in infertile women are caused by an association between fat and hyperinsulinemia, hyperandrogenism, and abnormal hormone production, including leptin. 19 , 20 Factors related to nutrition and lifestyle that impact fertility encompass conditions such as anemia, weight imbalances, and smoking. The American Society for Reproductive Medicine emphasizes that 12% of infertility instances arise from being either underweight or overweight.…”
Section: Discussionmentioning
confidence: 99%
“…The numerous reproductive issues seen in infertile women are caused by an association between fat and hyperinsulinemia, hyperandrogenism, and abnormal hormone production, including leptin. 19 , 20 Factors related to nutrition and lifestyle that impact fertility encompass conditions such as anemia, weight imbalances, and smoking. The American Society for Reproductive Medicine emphasizes that 12% of infertility instances arise from being either underweight or overweight.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients who have secondary infertility had a mean age of 33.08 ± 4.17 years. A study conducted in 2010 by Nosheen et al ( 18 ) reported that the mean age in secondary infertility was 32 years, while Talib et al ( 19 ) reported in 2007 that the mean age of secondary infertility was 29.4 years in women. Factors related to nutrition and lifestyle that impact fertility encompass conditions, such as weight imbalances, anemia, and smoking.…”
Section: Discussionmentioning
confidence: 99%